(x+1)+(x+2)=

Simple and best practice solution for (x+1)+(x+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+1)+(x+2)= equation:


Simplifying
(x + 1) + (x + 2) = 0

Reorder the terms:
(1 + x) + (x + 2) = 0

Remove parenthesis around (1 + x)
1 + x + (x + 2) = 0

Reorder the terms:
1 + x + (2 + x) = 0

Remove parenthesis around (2 + x)
1 + x + 2 + x = 0

Reorder the terms:
1 + 2 + x + x = 0

Combine like terms: 1 + 2 = 3
3 + x + x = 0

Combine like terms: x + x = 2x
3 + 2x = 0

Solving
3 + 2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 2x = 0 + -3

Combine like terms: 3 + -3 = 0
0 + 2x = 0 + -3
2x = 0 + -3

Combine like terms: 0 + -3 = -3
2x = -3

Divide each side by '2'.
x = -1.5

Simplifying
x = -1.5

See similar equations:

| 3y+5x=144 | | 2-5[5-(4y-6)]= | | 0.36/0.02 | | 4b+11=39 | | 2x(3x-4)=2(6x+8) | | 15+5=30 | | 8y-1=14+5y | | 3m=5m+8 | | k-3=4k-15 | | ln(2x+3)+ln(x-9)-2lnx=0 | | d^2+18d+63=0 | | 78.5*17= | | 70=(x-3)(x) | | 96=(x+4)(x) | | (2x-3)(7x+2)=0 | | =4-3+40 | | (8x^2+5x-6)(-3x)=0 | | x+(-6)=16 | | 10x^2-100+160=0 | | 6x+7=1-4x | | (15x^2-13x-7)=0 | | 2(4x-9)+x=180 | | (3x^2-5x-2)+(9x^2-3x+3)=0 | | 42b^2-43b-7=0 | | 12x+13=6x+139 | | 35=7/5t | | iz+(3+2i)z-1+3i=2z-i | | 3x+8y=32 | | 3iz+z+4i-1=0 | | 9x+4=6x+22 | | (11x^2-4x+1)-(-x^2+5x-7)=0 | | 4+91x=52x+7 |

Equations solver categories